If x + a is a factor of 3x² - mx - nx prove that a = m+n/3
Answers
Answered by
2
Answer:
a=(m+n) /3
Step-by-step explanation:
F(x) =3x²-mx-nx
G(x) =x-a
It is given that F(x) is divisible by G(x), thus from remainder their
F(a) =0
3a²-ma-na=0
3a²=ma+na
3a²=a(m+n)
Dividing by a on both sides
3a=m+n
a=(m+n) /3.
Hence proved
Answered by
1
Answer:
F(x) =3x²-mx-nx
G(x) =x-a
From remainder theorem,
3a²-ma-na=0
3a²=ma+na
3a²=a(m+n)
Dividing by a on both sides
3a=m+n
a=(m+n) /3.
HOPE IT HELPS YOU
PLEASE MARK ME AS THE BRAINLIEST
Similar questions
English,
6 months ago
Social Sciences,
6 months ago
Computer Science,
6 months ago
English,
1 year ago
Physics,
1 year ago